Cardiovascular disease and depression: a narrative review - Li, Xinzhong; Zhou, Jiahui; Wang, Min; Yang, Chengmin; Sun, Guibo (Frontiers in Cardiovascular Medicine, 2023)
In clinical practice, it is frequently observed that cardiac and psychological disorders frequently co-occur, leading to the emergence of a field known as cardiovascular disease with depression. Depression, in particular, poses a remarkable risk for the evolution of cardiovascular disease and intimately relates to adverse cardiovascular outcomes and mortality. Moreover, individuals who are depressed exhibit a higher susceptibility to developing cardiovascular disease compared to those in good health. Patients diagnosed with cardiovascular disease with depression disease face a heightened risk of mortality within a five-year timeframe, and their prognosis remains unsatisfactory even after receiving treatment targeting a single disorder, with a notable recurrence rate. Psychological interventions in conjunction with medications are commonly employed in clinical settings for treating patients with cardiovascular disease and depression diseases, albeit with limited effectiveness and unfavorable prognosis. Traditional Chinese medicine(TCM), such as Shuangxinfang, Chaihujialonggumuli, and Yixin Ningshen Tablet, etc, have been reported and have Therapeutic effects in patients with cardiovascular disease combined with depression. Despite numerous articles documenting a notable association between heart disease and depression, there exists a dearth of studies elucidating the precise pathogenesis and target of action for cardiovascular disease with depression diseases. This article endeavors to consolidate the epidemiological data, potential pathogenic mechanisms, and available treatment modalities for cardiovascular disease with depression diseases. Its primary objective is to unveil plausible co-morbid mechanisms and suitable treatment approaches, thereby offering novel insights for the prevention, diagnosis, and management of cardiovascular disease with depression diseases.